Effect of fiber type and content on mechanical properties of microbial solidified sand - Zhang, Xiaogang; Zheng, Chao; Xiong, Kangwei; Yang, Kun; Liang, Shihua (Frontiers in Materials, 2023)
Fibers are applied to construction works to improve the strength and brittle failure of the soil.In this paper, fibers with a length of 6 mm are added to the microbial cemented sand, and fiber types and content are research variable. Unconfined compressive strength (UCS), permeability coefficient, water absorption rate, dry density, and calcium carbonate precipitation of the solidified sand were tested. The physical and mechanical properties of fiber types and content on the immobilization of microorganisms were also analyzed from the micro-macro perspective. Results are presented as follows. The UCS of the Microbial induced calcium carbonate precipitation (MICP) treated sand increases first and then decreases with the increasing fiber content. This phenomenon is due to the promotion of calcium carbonate precipitation by short fiber reinforcement, the limited movement of the sand particles caused by the formed network between the fibers, and the enhanced strength of the microbial solidified sand. However, the agglomeration caused by additional fibers leads to the uneven distribution of calcium carbonate and the reduction in strength. The optimum fiber contents of polypropylene, glass, polyvinyl alcohol, and basalt fibers are 0.4%, 0.2%, 0.2%, and 0.1%, respectively.